2016
DOI: 10.1111/tpj.13193
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐directed DNA methylation efficiency depends on trigger and target sequence identity

Abstract: SUMMARYRNA-directed DNA methylation (RdDM) in plants has been extensively studied, but the RNA molecules guiding the RdDM machinery to their targets are still to be characterized. It is unclear whether these molecules require full complementarity with their target. In this study, we have generated Nicotiana tabacum (Nt) plants carrying an infectious tomato apical stunt viroid (TASVd) transgene (Nt-TASVd) and a non-infectious potato spindle tuber viroid (PSTVd) transgene (Nt-SB2). The two viroid sequences exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
(134 reference statements)
0
15
0
1
Order By: Relevance
“…In this regard, recent data have demonstrated that DNA methylation can also be modulated by DCL-independent siRNAs ( Yang et al. , 2016 ; Dalakouras et al. , 2016 ; Ye et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent data have demonstrated that DNA methylation can also be modulated by DCL-independent siRNAs ( Yang et al. , 2016 ; Dalakouras et al. , 2016 ; Ye et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, siRNAs derived from both nuclear and chloroplastic viroids can direct silencing of the host plant mRNAs through sequence-specific cleavage and degradation ( Navarro et al, 2012 ; Adkar-Purushothama et al, 2015 , 2018 ; Adkar-Purushothama and Perreault, 2018 ), although viroids can also indirectly impact on the host gene expression at both post-transcriptional and transcriptional levels ( Castellano et al, 2015 ; Tsushima et al, 2015 ; Torchetti et al, 2016 ; Zheng et al, 2017c ). Notably, nuclear viroids can also trigger de novo RNA-directed DNA methylation of the transgenes containing viroid sequences ( Wassenegger et al, 1994 ; Dalakouras et al, 2016 ). Whether or not viroid-derived 24-nt siRNAs are involved in this RdDM process remains unclear ( Dalakouras et al, 2016 ).…”
Section: Biogenesis and Function Of Viral Sirnasmentioning
confidence: 99%
“…Notably, nuclear viroids can also trigger de novo RNA-directed DNA methylation of the transgenes containing viroid sequences ( Wassenegger et al, 1994 ; Dalakouras et al, 2016 ). Whether or not viroid-derived 24-nt siRNAs are involved in this RdDM process remains unclear ( Dalakouras et al, 2016 ).…”
Section: Biogenesis and Function Of Viral Sirnasmentioning
confidence: 99%
“…RdDM efficiency is affected by the quality of the trigger RNA, i.e. sequence identity between the trigger and the target [18]. Interestingly, in contrast to the dramatic reduction in DNA methylation in dcl2/3/4 compared to the WT, P4 RNA levels in dcl2/3/4 are comparable to 24-nt siRNA levels in the WT [4,68].…”
Section: Do P4 Rnas Mediate Dna Methylation?mentioning
confidence: 99%